Działalność samorządu lekarskiego w zakresie doskonalenia zawodowego na przykładzie Wielkopolskiej Izby Lekarskiej - KORDEL, Piotr; KORDEL, Krzysztof; SAJ, Marek (Przegląd Politologiczny, 2018)
The issue of the continuous improvement of professional qualifications by medical doctors is of utmost importance both from the point of view of doctors and their patients. Acquiring new knowledge and skills is an important element of a doctor’s professional career. A doctor who raises his qualifications guarantees better medical care for a patient. The professional self-governing body of doctors constitutes a significant element in the postgraduate education of doctors. It participates in the education of interns and in the procedure of acquiring the title of specialist. It also supervises and organizes the process of doctors’ mandatory continuous education. A majority of the tasks related to doctors’ professional education is performed by regional chambers. The Wielkopolska Medical Chamber organizes training sessions and courses for its members, which are one of the forms of fulfilling the requirement of professional improvement, reimburses a portion of the costs borne by the doctors in connection with improving their professional qualifications, and it establishes cooperation with domestic and foreign academic institutions to provide doctors from Wielkopolska with an opportunity to partake in training. These activities of the medical association, combined with the organs of professional liability of doctors, allow the patients to hope that when visiting a doctor they encounter a specialist who will take the utmost care of them.